Pemanfaatan Media Sosial sebagai Sarana Promosi: Pelatihan Pembuatan Konten Digital bagi UMKM Upaya Peningkatan Pendapatan - Harnavela Sofyan; Laila Fitri Agnaeni; Hendi Aidil Fitri (Universitas Perjuangan Tasikmalaya, 2026)
The development of digitalization is increasingly widespread nowadays. It cannot be denied that the development of digitalization has spread to various sectors of human life, starting from how to communicate, how to obtain information, to how someone sells and buys. One of the advances in digitalization that has had a big impact is the presence of social media. Currently social media is used as a promotional tool. MSMEs are competing to create interesting content, which of course is expected to have an impact on increasing income. This service is carried out with the aim of improving the skills of regional MSMEs so they can create interesting promotional content. Held from 28 September - 30 September 2025. The method used in this service is an explanation of what interesting content is, discussions with MSMEs, as well as direct practical simulations in creating interesting promotional content. This dedication produces output in the form of content that is uploaded on social media that is more interesting and sells so that it has a significant impact on income. MSMEs also respond to this service process actively and responsivelyso that the process can run smoothly.